An experimental study on machining of SiC reinforced MMCs - Pramanik, Alokesh; Zhang, Liangchi; Arsecularatne, Joseph (Ibaraki University, Ibaraki, Japan, 2006)
This paper presents an experimental study on turning of metal matrix composite (MMC) with poly-crystalline diamond tool (PCD). Experiments were carried out on an MMC work material for varying values of depth of cut, feed and cutting speed and, process parameters such as shear angle, cutting forces, surface roughness and residual stress were measured. These experimental results were then used to study the relations between the above process parameters and machining parameters. A relation between shear and friction angles was also established.